Synergistic effect of alfatoxin B1 and ochratoxin A in chick embryos - Rony Ray John (Centre for Excellence in Pathology, College of Veterinary and Animal Sciences, 2001)
The present study was taken up to investigate the synergistic effects of the mycotoxins AFBl and OA on chick embryos, the variations in the susceptibility to the toxins both individually and in combination.